A terminologia da pesca artesanal no Baixo Tocantins - RIBEIRO, Janice Miranda (2024)
This Course Completion Work (TCC) proposes the elaboration of a Terminological Glossary of Artisanal Fishing practiced in the municipalities of Igarapé – Miri/PA (Panacauera River, rural area) and Barcarena/PA (Vila do Conde, urban area), composed of 204 entries (terms - entry) and their terminological variants (lexical, topoletal and morphosyntactic), are analyzed, registered and classified linguistically, following the theoretical-methodological assumptions of Lexicology, Terminology/Terminography and Socioterminology. The terms (specialized lexias) that make up the Terminological Glossary of Artisanal Fishing1 were extracted from 10 (ten) oral narratives of artisanal fishermen, professionals who work in artisanal fishing and use small and medium-sized wooden vessels, in two distinct regions of the lower Tocantins, namely Rio Panacauera, rural area and Vila do Conde, urban area districts of Igarapé-Miri/PA and Barcarena/PA, respectively. With regard to field linguistics, we used as a guide, the data collection techniques adopted by the ALiPA Project and Project ALiB with some adaptations. This time, 10 (ten) artisanal fishermen were enrolled who work for more than 05 (five) years in the trade, born and raised or residing in the locality for more than 10 (ten) years in the researched speech communities. For the collection of data, the following techniques were applied: 10 (ten) interviews with the 10 (ten) informants; digital recordings in MP3 format of 10 (ten) oral narratives; application of a semantic-lexical questionnaire (QSL) with questions related to the universe of fishing handmade; partial graphematic transcription of excerpts from the informants' speeches where the terms are realized morphosyntatically, for the composition of the terminological glossary proposed. When analyzing the corpus collected, we found terminological variants topoletal, lexical and morphosyntactic conditioned by social and geographic factors education, age and region.